Clinical and Basic Research on Renshen Yangrong Decoction - Sheng, Wei; Wang, Yun; Li, Jiang-Bo; Xu, Hua-Shan (Frontiers in Nutrition, 2019)
Renshen Yangrong Decoction has been used to treat asthenic disease symptoms, such as exhaustion, and qi and blood deficiency diseases. It not only promotes hematopoietic function and improve immune functions, but also alleviates coronary heart diseases, diabetic complications, malignant tumor, and brain injury. It has satisfactory curative effect on sleep disorders and fatigue. Herein, we provide an overview of fundamental research on Renshen Yangrong Decoction focusing on its hematopoietic and immune functions and the status of clinical research with regard to the above-mentioned diseases in recent years.